Pengaruh Strategi Marketing Mix Terhadap Keputusan Pengunjung Wisata Pemandian Tasnan Kabupaten Bondowoso - Feti Fatimah; Fadhol Ibrahim; Nursaidah Nursaidah (JURNAL MANAJEMEN DAN BISNIS INDONESIA, 2022)
The purpose of this research to know the impact of the marketing mix strategy on the decision of visitors to the Tasnan Pool in Bondowoso Regency. The population of this research is the visitors of the Tasnan Pool, Bondowoso Regency, whose countless. The sampling using method Purposive Sampling. Sampling obtained from assessment 75 respondents. The data used in this study are primary data. The analysis system used is multiple linear regression analysis to know the effect of the independent variable on the dependent variable. The results showed that the product, price, place, and promotion influence the decision of visitors to the Tasnan Pool in Bondowoso Regency.